Analysis Of The Legislative Function Of The House Of Representatives In The Process Of Forming Law Number 3 Of 2025 Concerning Amendments To Law Number 34 Of 2004 Concerning The Indonesian National Armed Forces: Analisis Fungsi Legislasi Dewan Perwakilan Rakyat dalam Proses Pembentukan Undang-Undang Nomor 3 Tahun 2025 tentang Perubahan atas Undang-Undang Nomor 34 tahun 2004 tentang Tentara Nasional Indonesia - Siraj, Lutfi Nabil; Saputra, Dewa; Paizal, Paizal (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Constitutional amendments shifted lawmaking authority to the legislature, positioning it as the central actor in democratic legal formation. Specific Background: The formation of Law Number 3 of 2025 concerning the Indonesian National Armed Forces reflects a contested legislative process marked by debates on transparency, participation, and accountability. Knowledge Gap: There remains limited critical examination of how legislative functions operate in practice when confronted with accelerated procedures and strong executive involvement. Aims: This study analyzes the implementation of the legislative function in the lawmaking process, focusing on transparency, public participation, and accountability within civil–military relations. Results: The findings reveal that the legislative process did not operate optimally, characterized by rapid deliberation, limited transparency, and restricted public involvement, alongside indications of dominant executive influence that weakens representative functions and obscures civilian supremacy principles. Novelty: The study offers a contextual and specific analysis of contemporary legislative dynamics by examining procedural deviations and their relation to deliberative democracy and good governance principles. Implications: These findings underline the necessity of strengthening transparency, expanding meaningful public participation, and reinforcing legislative accountability to preserve democratic legitimacy and maintain the quality of lawmaking processes. HIGHLIGHTS• Accelerated deliberation reduced procedural openness and public engagement• Executive dominance constrained representative institutional performance• Procedural deviations revealed inconsistency with deliberative democratic principles KEYWORDSLegislation; Transparency; Participation; Accountability; Democracy